2022
DOI: 10.3201/eid2809.220476
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Emergence and Spread of SARS-CoV-2 Omicron Variant in Large and Small Communities by Wastewater Monitoring in Alberta, Canada

Abstract: Wastewater monitoring of SARS-CoV-2 enables early detection and monitoring of the COVID-19 disease burden in communities and can track specific variants of concern. We determined proportions of the Omicron and Delta variants across 30 municipalities covering >75% of the province of Alberta (population 4.5 million), Canada, during November 2021–January 2022. Larger cities Calgary and Edmonton exhibited more rapid emergence of Omicron than did smaller and more remote municipalities. Notable exceptions were Banff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…To estimate the VOC proportion (%), we first calculated the abundance (copies/ml) of each VOC from the copies per reaction using an established methodology 18 . Then, we estimated the VOC proportion (%) of Delta (R203M mutation) or Omicron (R203K/G204R mutation) in RNA extracted from hospital wastewater by calculating the ratio of the abundance of a target mutation over the sum of the abundance of Omicron signal (R203K‐G204R assay) and Delta signal (R203M assay) 27 . All calculations for estimation of VOC proportions are described in the Supporting Information Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the VOC proportion (%), we first calculated the abundance (copies/ml) of each VOC from the copies per reaction using an established methodology 18 . Then, we estimated the VOC proportion (%) of Delta (R203M mutation) or Omicron (R203K/G204R mutation) in RNA extracted from hospital wastewater by calculating the ratio of the abundance of a target mutation over the sum of the abundance of Omicron signal (R203K‐G204R assay) and Delta signal (R203M assay) 27 . All calculations for estimation of VOC proportions are described in the Supporting Information Materials.…”
Section: Methodsmentioning
confidence: 99%
“…VOC detection was assessed with the N200 multiplex RT-qPCR assay for the presence of N200-universal, Delta (R203M) and Omicron (R203K/G204R) signals as previously described. 27,28 The N200 assay is a probe-based multiplex assay that targets the region encoding amino acids 199-202 within the nucleocapsid gene (N) which have been associated with variants of SARS-CoV-2. 28 Serial dilutions of the TWIST AR-S SARS-CoV-2 RNA control 14 and control 23 were run in triplicate on 96-well PCR plates to produce standard curves used to quantify gene copies containing R203K/G204R and R203M mutations, respectively.…”
Section: Rt-qpcr and Voc Rt-qpcr Analysismentioning
confidence: 99%
“…Our wastewater sequencing and dPCR molecular assays corroborated the synchronous introduction of Omicron in the community. Interestingly, wastewater surveillance studies in AB, Canada found that the introduction of Omicron was earlier in communities closer to dense population centers and tourist attraction locations which attract international travelers ( 41 ). Similarly, the time of initial establishment and subsequent rise of Omicron in MA, USA was found to be earlier and more rapid at institutes of higher education likely owing to dense dormitory style housing and differences in social behavior ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12,24 In short, two regions of the nucleocapsid gene (N1 and N2) were used to quantify total SARS-CoV-2 RNA copies/mL in every wastewater sample. [25][26][27] We also analyzed variants of concern (VOC), including Delta, Omicron (BA.1, and BA.2) using the N200 multiplex assay 24,28 or 69/70del assay 29 for a subset of samples for WWTP (44 samples), RH1 (18 samples), SO (18 samples), NW (17 samples), and NE (9 samples) from November 28, 2021-April 27, 2022. BCoV (Bovine Coronavirus) was analyzed as an internal spike control, and PMMoV (Pepper Mild Mottle Virus) was analyzed as a potential human feces biomarker.…”
Section: Quantitative Rt-qpcrmentioning
confidence: 99%
“…This solution was then passed through a Zymo Spin™ III-P silica column (Zymo Research, USA). 24 More details can be found in the Supplement.…”
Section: Sample Processing and Rna Extractionmentioning
confidence: 99%